Effects of ascorbic acid supplementation on oxidative stress markers in healthy women following a single bout of exercise - Manita Yimcharoen (2019)
© 2019 The Author(s). Background: Ascorbic acid is a water-soluble chain breaking antioxidant. It scavenges free radicals and reactive oxygen species (ROS), which are produced during metabolic pathways. Exercise can produce an imbalance between ROS and antioxidants, leading to oxidative stress-related tissue damages. This study was designed to determine the effects of ascorbic acid supplementation on circulating biomarkers of oxidative stress and muscle damage following a single bout of exercise. Methods: In a crossover design with a 1 wk. wash-out period, 19 healthy women performed 30 min moderate-intensity cycling after ingesting 1000 mg of ascorbic acid (AA) or placebo. Blood samples were taken immediately before, immediately after and 30 min post-exercise to determine plasma albumin, total protein, glucose, oxidative stress and muscle damage markers. Results: Plasma albumin and total protein levels increased immediately after exercise in placebo alongside slight reductions in glucose (p = 0.001). These effects were absent in AA cohort. Ferric reducing ability of plasma and vitamin C levels in AA cohort significantly increased after exercise (p < 0.05). Superoxide dismutase activity was significantly elevated after exercise (p = 0.002) in placebo but not AA. Plasma malondialdehyde did not change after exercise in placebo but was significantly decreased in AA (p < 0.05). The exercise protocol promoted slight muscle damage, reflected in significant increases in total creatine kinase in all subjects after exercise. On the other hand, plasma C-reactive protein and lactate dehydrogenase remained unchanged. Conclusion: Supplementation with ascorbic acid prior exercise improves antioxidant power but does not prevent muscle damage.